Strategi Guru dalam Meningkatkan Gerakan 6 S di Kelas IV C SDN 64/I Muara Bulian - Ahmad Hariandi; Ira Rohaya Sitio; Putri Ramadhani; Adi Priyono; Yuli Susanti (JIP Jurnal Ilmiah PGMI, 2020)
The goals is to describe strategies that class teacher use for increase school 6 S movement in class IV C Elementary School Number 64/I Muara Bulian. Qualitative descriptive that used. For collecting the data were used to observation and interview. Interview with class IV C teacher in Elementary School Number 64/I Muara Bulian, analysis data used interactive model (Miles and Huberman) and for tested the validity of data that use triangulation data. From this research there are five strategies that class IV C Teacher use in Elementary School Number 64/I Muara Bulian, such as wall poster for meaningful learning and practice things in the wall poster sentences.